2016
DOI: 10.4103/1008-682x.167720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quercetin and resveratrol in the prevention of injury due to testicular torsion/detorsion in rats

Abstract: Quercetin (QE) and resveratrol (RSV) are powerful antioxidants with the potential to protect the testes against ischemia/reperfusion (I/R) injury. We compared their effects in testicular torsion/detorsion (T/D) in adult rats. Twenty-four male Wistar rats were divided into four groups: sham (group A), T/D (group B), T/D treated with QE (group C), and T/D treated with RSV (group D). QE (20 mg kg−1) and RSV (20 mg kg−1) were injected intra-peritoneally at 60 min of torsion. After 90 min of surgically induced tors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Chi et al. (2016) have shown preventive impacts of QCT and resveratrol against testicular torsion/detorsion through enhancing antioxidant levels and reducing lipid peroxidation in rats. Yelumalai et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chi et al. (2016) have shown preventive impacts of QCT and resveratrol against testicular torsion/detorsion through enhancing antioxidant levels and reducing lipid peroxidation in rats. Yelumalai et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, dilated congested blood vessels in the interstitium, mild disorganisation in the seminiferous tubules, decreased spermatid and edema were found in the ETD-50 group, which suppressed oxidants and cytokines milder than those in the ETD-100 group. Torsion-detorsion has been experimentally demonstrated to lead to pathological changes, including disorganisation in the seminiferous tubules, necrosis of the germinal cells, decreased spermatozoa [ 39 ] and interstitial edema [ 4 ]. In their study, Minutoli et al histopathologically showed severe damage in the testes caused by I/R [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms of testicular T/D center around testicular IRI, in which torsion results in ischemic damage and detorsion leads to enhanced blood flow and subsequent reperfusion injury, resulting in spermatogenic cell apoptosis and the disruption of spermatogenesis, eventually leading to testicular dysfunction and infertility [23, 24]. The two major factors affecting testicular damage are the duration and degree of spermatic cord torsion, with testicular salvage rates from manipulative and operative reduction ranging from 42% to 88% [25, 26].…”
Section: Discussionmentioning
confidence: 99%